2023
DOI: 10.35633/inmateh-70-50
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low-Frequency High-Voltage Pulsed Electric Fields on Germination Characteristics of Aged Rice Seeds

Tiangang HOU,
Zhenyu WANG,
Mingce ZHAO
et al.

Abstract: In this study, the effects of different electric field parameters on the germination characteristics of aged rice seeds were determined via low-frequency high-voltage pulsed electric field (LH-PEF) treatment. The Design-Expert software was used to design a rotating combination test, and response surface analysis was used to optimize five germination characteristics of rice seeds. The optimal treatment voltage was 13 kV and the optimal treatment time was 32.72 min. The results show that, under the optimal treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…The beneficial biological effects can be produced by treating seeds of a certain state (including size, water content, and vitality) with the appropriate electric field type and process parameters. When using low-frequency high-voltage PEF treatment of aged rice seeds with a voltage of 13 kV and time of 32.72 min, the GP, GR, GI, and VI of seeds can be significantly improved [30]. Akdemir et al found that, when wheat seeds were treated with PEF at 1.07-17.28 J, the GR and emergence rates were significantly increased by 10% and 28% [20].…”
Section: Suitable Pef Treatment Can Promote Seed Germination Of Scute...mentioning
confidence: 99%
“…The beneficial biological effects can be produced by treating seeds of a certain state (including size, water content, and vitality) with the appropriate electric field type and process parameters. When using low-frequency high-voltage PEF treatment of aged rice seeds with a voltage of 13 kV and time of 32.72 min, the GP, GR, GI, and VI of seeds can be significantly improved [30]. Akdemir et al found that, when wheat seeds were treated with PEF at 1.07-17.28 J, the GR and emergence rates were significantly increased by 10% and 28% [20].…”
Section: Suitable Pef Treatment Can Promote Seed Germination Of Scute...mentioning
confidence: 99%